Perceiving Self, Others, and Events Through a Religious Lens: Mahayana Buddhists vs. Christians - Huang, Tsung-Ren; Wang, Yi-Hao (Frontiers in Psychology, 2019)
Are all religions essentially the same? Are believers of different religions heading in the same mental direction? To answer these questions from a sociopsychological perspective on the effects of religious beliefs, we compared social sensitivity and causal attribution styles between Mahayana Buddhists, who practice unbiased love and compassion towards every being, and Christians, who pursue a union with God. Despite a similar cultural background, sex ratio, age distribution, socioeconomic status, and fluid intelligence level, these two religious groups in Taiwan showed opposite tendencies when inferring the mental states of others—as religiosity increased, the theory of mind ability increased in Mahayana Buddhists but decreased in Christians. Furthermore, these two religious groups showed opposite tendencies of attributional style—as religiosity increased, self-serving bias decreased in Buddhists but increased in Christians. These marked religiosity-dependent, sociopsychological effects suggest that different religions may shape or attract their followers who are moving in quite distinct mental directions.